Health system readiness and the implementation of rectal artesunate for severe malaria in sub-Saharan Africa: an analysis of real-world costs and constraints. Issue 2 (February 2023) - Lambiris, Mark J; Venga, Guy Ndongala; Ssempala, Richard; Balogun, Victor; Galactionova, Katya; Musiitwa, Michael; Kagwire, Fred; Olosunde, Oluseyi; Emedo, Emmanel; Luketa, Sylvie; Sangare, Moulaye; Buj, Valentina; et al.
Summary: Background: Rectal artesunate, an efficacious pre-referral treatment for severe malaria in children, was deployed at scale in Uganda, Nigeria, and DR Congo. In addition to distributing rectal artesunate, implementation required additional investments in crucial but neglected components in the care for severe malaria. We examined the real-world costs and constraints to rectal artesunate implementation. Methods: We collected primary data on baseline health system constraints and subsequent rectal artesunate implementation expenditures. We calculated the equivalent annual cost of rectal artesunate implementation per child younger than 5 years at risk of severe malaria, from a health system perspective, separating neglected routine health system components from incremental costs of rectal artesunate introduction. Findings: The largest baseline constraints were irregular health worker supervisions, inadequate referral facility worker training, and inadequate malaria commodity supplies. Health worker training and behaviour change campaigns were the largest startup costs, while supervision and supply chain management accounted for most annual routine costs. The equivalent annual costs of preparing the health system for managing severe malaria with rectal artesunate were US2·63, 2·20, and 4·19 per child at risk and 322, 219, and 464 per child treated in Uganda, Nigeria, and DR Congo, respectively. Strengthening the neglected, routine health system components accounted for the majority of these costs at 71·5%, 65·4%, and 76·4% of per-child costs, respectively. Incremental rectal artesunate costs accounted for the minority remainder. Interpretation: Although rectal artesunate has been touted as a cost-effective pre-referral treatment for severe malaria in children, its real-world potential is limited by weak and under-financed health system components. Scaling up rectal artesunate or other interventions relying on community health-care providers only makes sense alongside additional, essential health system investments sustained over the long term. Funding: Unitaid. Translation: For the French translation of the abstract see Supplementary Materials section.